2021
DOI: 10.3390/ijms22189741
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Workflow for the Identification of Novel Fragments Acting as Inhibitors of the Activity of Protein Kinase CK1δ

Abstract: Fragment-Based Drug Discovery (FBDD) has become, in recent years, a consolidated approach in the drug discovery process, leading to several drug candidates under investigation in clinical trials and some approved drugs. Among these successful applications of the FBDD approach, kinases represent a class of targets where this strategy has demonstrated its real potential with the approved kinase inhibitor Vemurafenib. In the Kinase family, protein kinase CK1 isoform δ (CK1δ) has become a promising target in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 61 publications
(66 reference statements)
2
15
0
Order By: Relevance
“…Our model is disposed on a triangle conformation, wherein the first one of the vertexes is situated in the buried region, the second one is situated interacting with the adenine region, and the third one is situated at the phosphate binding region. This model is compatible with the one proposed by Bolcato et al for CK1δ inhibitors [40], but implies improvement since our analysis revealed additional hotspots.…”
Section: Discussionsupporting
confidence: 92%
“…Our model is disposed on a triangle conformation, wherein the first one of the vertexes is situated in the buried region, the second one is situated interacting with the adenine region, and the third one is situated at the phosphate binding region. This model is compatible with the one proposed by Bolcato et al for CK1δ inhibitors [40], but implies improvement since our analysis revealed additional hotspots.…”
Section: Discussionsupporting
confidence: 92%
“…Encouraged by the results of our benchmark runs, we decided to perform a prospective run with the IFP CS protocol, applying the same operating conditions as before. This time, the starting library was modified to add to the compounds used for the benchmark runs seven fragment ATP-competitive CK1δ inhibitors identified during a previous virtual screening campaign from our laboratory ( Bolcato et al, 2021 ). The idea behind this run was to evaluate the ability of our IFP CS scoring protocol to generate interesting novel potential CK1δ inhibitors derived from in-house, readily available compounds.…”
Section: Resultsmentioning
confidence: 99%
“… Chemical structure of the seven fragment CK1δ inhibitors derived from the work of Bolcato et al (2021) . …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further investigate this aspect, we expanded our computational analysis by performing a molecular dynamics (MD) experiment, in which each crystallographic ligand was left free to move for 5ns (three replicas per system). This approach (known as "MD post-docking") has already become part of our computational protocol [27,28] and is based on the fact that the conformations of the ligands, which are less prone to be displaced from their initial posi-tion during the simulation, are related to higher stability and binding strength with the target. In the case presented, this principle was applied directly to the crystallographic conformations of the ligands rather than to docking poses.…”
Section: Introductionmentioning
confidence: 99%